P-9 Reduction of risk factors for cardiovascular diseases and long lasting walking practice following one year of walking guided by exercise physiologists. a study on 326 sedentary subjects. (18th November 2016) - Mandini, S; Collini, G; Lavezzi, E; Mazzoni, G; Grazzi, G; Conconi, F
Abstract : Objectives: The aims of the study were to organise a program of guided walking for sedentary subjects, to analyse the changes of some risk factors for cardiovascular diseases after one year of walking and to check the permanence of unsupervised walking practice months after the program was over. Methods: 650 adults and elderly subjects, declaring only occasional physical activity, were enrolled. Weight, height, waist circumference, systolic and diastolic blood pressure and walking speed (measured on a 100 metres course, at an intensity of 12-14 on the Borg scale) were determined at enrolment. Subjects were invited to walk as frequently as possible alone or with one of the several walking groups organised for the project. Walking groups were active five days a week with walking sessions of approximately one hour. The variables measured at enrolment were re-determined after one year. Sixteen month after the end of the project the participants completing the program fill in a questionnaire on the weekly walking hours they were still doing. Results: 326 subjects (212 women and 114 men) walked from three to seven days a week and completed the one-year project. After 12 months of walking, highly significant reductions of body weight, BMI, waist circumference, systolic and diastolic blood pressure and highly significant increase in walking speed were documented 1 (Table 1 ). Identical results were obtained for both women and men. Sixteen months after the end of the project 258 subjects declared 170 ± 110 minutes a week of independent walking (Figure 1 ), a time superimposable to the one indicated by the 2008 Physical Activity Guidelines for Americans. Conclusions: One year of guided walking has been followed by highly significant reductions of some risk factors for cardiovascular diseases and by a highly significant improvement of the walking speed. Sixteen months after the end of the project, 77% of the participants were independently maintaining the walking practice, indicating that guided walking is effective in permanently modifying the lifestyle of sedentary subjects. Acknowledgments: Supported by the Italian Ministry of Education and Scientific Research and the Ministry of Sport. References: Murphy MH, Nevill AM, Murtagh EM, Holder RL. The effect of walking on fitness, fatness and resting blood pressure: a meta-analysis of randomised, controlled trials. Prev Med . 2007;44 (5):377–85.